Effect of refrigeration assisted intercooler turbocharging on engine’s horse power effect of refrigeration assisted intercooler turbocharging on engine’s horse power - Arif, Saba; Naqvi, Syed Muhammad Afzal; Gill, Fahad Tariq; Qadeer, Adil; Taweekun, Juntakan; Noranai, Zamri; Kalvin, Roman (Penerbit Akademia Baru, 2021)
The stringent regulations on fuel saving and emissions reduction in the transportation sector have become game-raisers in the development of present internal combustion engines for road applications, even if under-the-hood space constraints, downsizing and down-weighting prevent from adopting radical changes in the engine layout. In current research, objective is to find a viable and pragmatic solution to reduce the turbo-charged engine intake air temperature by a large value as compared to traditional air-to-air intercoolers to increase Engine Horsepower. In undergoing research, a refrigerated intercooler is designed on the basis of refrigeration cycle, which further decreases the intake air temperature of the engine, resulting in increased horsepower, and improved Formula 1 lap times. Additionally, Formula 1, 2014 (V6 Turbo-Charged) Engine is used. According to the results, horse power of 1209.74HP is obtained by using refrigeration assisted intercooler. However, 1061HP is obtained for air to air intercooler. So, performance gain of 15 to 20% over present intake air cooling system in Formula 1 engine cars is successfully achieved. Additionally, Research will be utilized to decrease lap time in formula 1 racing cars.